The crystal structure of R3Fe0.1Ga1.6S7 chalcogenides (R – La, Ce, Pr and Tb) - Blashko, N.M.; Marchuk, O.V.; Fedorchuk, A.O. (Physics and Chemistry of Solid State, 2024)
The paper reports the study of the crystal structure of chalcogenides of the composition R3Fe0.1Ga1.6S7 (R = La, Ce, Pr and Tb) as promising materials predicted to possess interesting nonlinear optical and electrical properties. Samples of stoichiometric composition were synthesized by co-melting the elements in quartz containers evacuated to a residual pressure of 10–2 Pa at the maximum synthesis temperature of 1100 °C. The crystal structure of the chalcogenides La3Fe0.1Ga1.6S7 a = 10.1884(6) Å, c = 6.0515(4) Å, Ce3Fe0.1Ga1.6S7 a = 10.0864(4) Å, c = 6.0440(3) Å, Pr3Fe0.1Ga1.6S7 a = 9.9853(3) Å, c = 6.0648(2) Å and Tb3Fe0.1Ga1.6S7 a = 9.6692(7) Å, c = 6.0799(5) Å was studied by X-ray powder method. It was determined that the structure of the synthesized phases belongs to the hexagonal symmetry (La3CuSiS7 structure type; space group P63). The structure of the complex chalcogenides (A), (B), (C) and (D) is based on the R3Ga1.67S7 sulfides (R = La, Ce, Pr, and Tb) by substituting gallium atoms in the 2a sites with atoms of statistical mixture M10.57(2) Ga + 0.10(2) Fe, M20.56(1) Ga + 0.10(2) Fe, M3 0.61(8) Ga + 0.09(1) Fe and M4 0.57(2) Ga + 0.10(2) Fe, respectively. Rare earth atoms are localized in the 6c sites and center sulfur atoms to form trigonal prisms with an additional atom [R 3S13S21S3]. Atoms of statistical mixtures M1, M2, M3, M4 are localized in the 2a sites forming [M 6S2] octahedra. Ga atoms in the 2b sites are surrounded by four sulfur atoms [Ga 3S11S3].